Plectranthias kamii Randll, 1980 (Perciformes: Serranidae) collected from Bitung, North Sulawesi: first record from the Southwest Pacific Ocean - Peristiwady, Teguh; Du, Jianguo; Hukom, Frensly Damianus; Makatipu, Petrus Christianus; Loh, Kar Hoe (Springer Verlag, 2018)
Three specimens of the serranid fish (Serranidae), Plectranthias kamii Randall, 1980 were collected from fish market, Bitung, North Sulawesi on May and June 2010. Some morphological characters P. kamii is closely related to P. sheni, P. megalophthalmus, P. retrofasciatus, P. rubrifasciatus, P. knappi, P. helenae, P. pelicieri, P. jothyi, P. retrofasciatus and P. randalli in sharing of body width, upper jaw length, pelvic spine length and orbit diameter. Meristic count characters of P. kamii differ from P. sheni, P. pilicieri, P. megalophthalmus, P. retrofasciatus and P. rubrifasciatus in having more numerous dorsal spine (18 vs. 15–17) and below lateral line (33–34 vs. 29–33) and differ from P. megalophthalmus and P. rubrifasciatus in having more numerous pored scales in lateral line (13 vs. 14–15) and shorter of anal spine. The present anthiine fish collected from Bitung, Indonesia was described as new record and bringing the total number of species of this genus known in Indonesia to seven.